Adenocarcinoma do colo do útero: um verdadeiro desafio clínico - Santos,Fernanda (2018)
Overview and Aims: Cervical cancer is the fourth most frequent cancer in women worldwide, with 266.000 death cases in 2012. The epidermoid cancers are more prevalent, but the incidence of adenocarcinomas and its variants has increased over the past few decades, especially in young women. Problems impacting the diagnosis of cervical glandular lesions include reduced sensitivity of screening with cervical cytology, colposcopic inexperience and subtle colposcopic findings. This study aimed to evaluate in situ and invasive cervical adenocarcinoma cases with regards to relations between risk factors, prognostic factors and mortality. Study Design: Cross-sectional study. Methods: 28 women diagnosed with cervical adenocarcinoma, were revised. The diagnose was made at a tertiary center, from January 2009 to December 2015. Statistical analysis was performed by STATA 13.1 program. Results: Ten cervical adenocarcinoma in situ (AIS) and eighteen invasive adenocarcinoma (IA), were analyzed. It was identified statistical difference in the diagnostic age (AIS: median 39 years; IA: median 51 years), number of previous cervical cytologies (AIS: 80% performed screening vs IA: 50% no screening) and cytology findings (AIS: 63% Atypical glandular cells vs IA: 50% adenocarcinoma). There was no relation with obesity, hormonal contraception, smoking and number of sexual partners. It was identified statistical significance between prognosis and FIGO stage (55.6% Stage1). Five deaths were reported (IB1:1, IIA1: 2 e IVB:2) and also one successful pregnancy (IA1). Conclusion: In this study, it was not identified relation with risk factors and only FIGO stage statistically contributes to prognosis.